2021
DOI: 10.1038/s41467-021-25916-6
|View full text |Cite
|
Sign up to set email alerts
|

Nance-Horan Syndrome-like 1 protein negatively regulates Scar/WAVE-Arp2/3 activity and inhibits lamellipodia stability and cell migration

Abstract: Cell migration is important for development and its aberrant regulation contributes to many diseases. The Scar/WAVE complex is essential for Arp2/3 mediated lamellipodia formation during mesenchymal cell migration and several coinciding signals activate it. However, so far, no direct negative regulators are known. Here we identify Nance-Horan Syndrome-like 1 protein (NHSL1) as a direct binding partner of the Scar/WAVE complex, which co-localise at protruding lamellipodia. This interaction is mediated by the Ab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 42 publications
2
16
0
Order By: Relevance
“…5 a). Because of the distinct subcellular distribution of Rac1 in DB cells, immunocytochemistry was performed to detect the subcellular distribution of WAVE2 47 . Confocal microscopy revealed that WAVE2 was found to be localized to the cell periphery and co-localized with F-actin fibers and in WT and DKO cells, as illustrated by the increase of white pixels in merged images (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5 a). Because of the distinct subcellular distribution of Rac1 in DB cells, immunocytochemistry was performed to detect the subcellular distribution of WAVE2 47 . Confocal microscopy revealed that WAVE2 was found to be localized to the cell periphery and co-localized with F-actin fibers and in WT and DKO cells, as illustrated by the increase of white pixels in merged images (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This included Hjurp , which can regulate double-strand DNA repair ( 32 34 ), neurogenesis factors Dll3 and Arx ( 35 , 36 ), as well as neuronal cell migration regulator Nhsl1 a (Fig. 5D and data S22) ( 37 ). Thus, in addition to its oncogenic mutator functions via sequence-specific somatic mutagenesis, Pgbd5 may also regulate neuronal progenitor cell development and DNA damage repair.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, targeting Rac1-Scar/Wave-Arp2/3 would help to inhibit tumor progression. Another study shows that Rac1-Scar/Wave-Arp2/3 can be negatively regulated by Nance-Horan Syndrome-like 1 protein (NHSL1), which directly interacts with Scar/Wave, thus reducing cell lamellipodia stability and migration efficiency [ 94 ]. As a local inhibitor of lamellipodia induced by Scar/Wave, CYFIP-related Rac interactor (CYRI) can compete with Scar/Wave to bind Rac1, which is important in regulating pseudopod complexity and dynamics [ 95 ].…”
Section: Molecular Mechanisms Of Cell Migration Regulated By Rac1mentioning
confidence: 99%